Implementation of state business support programs: current situation, analysis and proposals - Atabayeva, A.K.; Lebayev, N.M.; Aliyev, M.K.; Alisheva, D.E.; Baikenzhina, Sh.T. (BUKETOV BUSINESS REVIEW, 2023)
Object: To determine the factors affecting the development of medium and small businesses, as well as to investigate the degree of influence of state support on entrepreneurship in the Republic of Kazakhstan. Methods: The study used statistical methods of analysis, including multiple correlation-regression modeling. Findings: The authors put forward and tested hypotheses about the presence of a relationship between the dependent variable “Share of SMEs in GDP” and such factors as “The amount of funds for support for SMEs”, “Employed in the SME”, “Number of able-bodied population”, “Index of prices for food products”, “GDP per capita”, “Level of youth unemployment”. To prove or refute these hypotheses, a correlation and regression analysis was carried out. A check of the variable model for multicollinearity has been checked and the determination coefficient is calculated. The value of the r-quadratic determination coefficient for the dependent variable “SME share in GDP” is of high value (0.96), which suggests that the factors included in the model are well described and have a high degree of influence on it. In general, the regression analysis showed that the resulting model is adequate and reliable. Statistically significant coefficients were determined for the variables “Able-bodied population”, “GDP per capita”, “Youth unemployment rate”, that is, the listed indicators play a significant role in changing the “Share of SMEs in GDP”. At the same time, the factors “Number of working-age population” and “Unemployment rate among youth” have an inverse relationship with the indicator “Share of SMEs in GDP”. Conclusions: regression analysis showed that in Kazakhstan there are certain problems in the implementation of state policy in relation to the development of entrepreneurship. This fact is confirmed by the results of the study. The main hypothesis about the impact of the “Amount of funds to support SMEs” on the indicator “Share of SMEs in GDP” was not confirmed. The presence of problems in the distribution of state resources requires constructive state measures to solve the existing problems.